Quality management system in implementation of outcome based education at faculty of mechanical engineering, universiti malaysia pahang - Muhamad, Mat Noor; Kadirgama, Kumaran; Mohd Ruzaimi, Mat Rejab; Mohd Shahrir Mohd, Sani; Md Mustafizur, Rahman; Ahmad Syahrizan, Sulaiman (2008)
This paper presents the implementation of outcome-based education (OBE) in terms of course delivery, assessment and evaluation at the Faculty of Mechanical Engineering, Universiti Malaysia Pahang (UMP). The implementation was formalized based on the quality management system (QMS) of the Faculty which is formulated its philosophy on OBE as well as on teaching and learning to facilitate the implementation. The process of implementation involved training the representatives, planning the implementation and formulating the outcomes. The conventional teaching approaches were modified to make a classroom participative in nature in order to achieve the outcomes. The aspects of delivery, assessment and evaluation are discussed.